2015
DOI: 10.7224/1537-2073.2014-001
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Placebo-Controlled Trial of Duloxetine for Central Pain in Multiple Sclerosis

Abstract: Background: Pain is common in multiple sclerosis (MS). Duloxetine has a potential therapeutic role in treating MS-related pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
(19 reference statements)
0
14
0
2
Order By: Relevance
“…They facilitate descending inhibition by blocking serotonin and noradrenaline reuptake [3,9]. They have been shown to be effective in peripheral diabetic neuropathy, painful peripheral neuropathy [8,13], and more recently in central neuropathic pain secondary to multiple sclerosis [50]. However, venlafaxine is not effective in post-herpetic neuralgia [13].…”
Section: Resultsmentioning
confidence: 99%
“…They facilitate descending inhibition by blocking serotonin and noradrenaline reuptake [3,9]. They have been shown to be effective in peripheral diabetic neuropathy, painful peripheral neuropathy [8,13], and more recently in central neuropathic pain secondary to multiple sclerosis [50]. However, venlafaxine is not effective in post-herpetic neuralgia [13].…”
Section: Resultsmentioning
confidence: 99%
“…Its safety has been confirmed in a 52-week study [ 34 ]. Further, it was shown that duloxetine improved central neuropathic pain compared to placebo in patients with multiple sclerosiss [ 35 ]. Duloxetine is approved in Japan for not only painful diabetic polyneuropathy and other chronic pain condition (i.e., osteoarthritis, chronic low back pain, and fibromyalgia), but also major depression.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Leijon et al (1989) 19 was also excluded from the quantitative synthesis as, in addition to having presented mean and standard deviations as central tendency and dispersion measures, the statistical analysis was performed with non-parametric tests, making these measures inappropriate. The 20 studies included pharmacological agents employed in the treatment of central pain in multiple sclerosis 20,21,22,23,24,25,26,27,28 , spinal cord injury 16,22,27,29,30 , stroke 15,[20][21][22]31 , and brachial plexus injury with avulsion 32 . They used as pharmacological agents pregabalin 20,21,22,31 , gabapentin 29 , duloxetine 26,27,30 , amitriptyline 19 , combinations of cannabidiol/delta-9-tetrahydrocannabinol (CBD/THC) 14, 24,32,33 , lamotrigine 14,15,24 , levetiracetam 15 , carbamazepine 19 , dronabinol 28 , and valproate 16 .…”
Section: Systematic Review Of the Literature And Formulation Of The Fmentioning
confidence: 99%